Developing a Research-Integrated PjBL Model and Descriptive Assessment for Laboratory and Science Process Skills - Khusna Arif Rakhman; Indra Cipta; Nurfatimah Sugrah; Dira Ayu Annisa; Ni Made Wiratini; Nurbaiti Kumendong (FKIP Universitas Lampung, 2026)
This study aims to describe the implementation of environmentally friendly chemistry lessons and projects and the associated levels of students’ laboratory and science process skills. The Research-Integrated Project-Based Learning (RPjBL) model was proposed as a framework for developing industrially applicable processes for the synthesis of silver nanoparticles (AgNPs) using bioreduction agents derived from nature. The model was developed using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model to describe the steps involved in synthesizing AgNPs. The sample consisted of 21 students who completed assessments of their laboratory and science process skills and their project performance. Expert reviews of the RPjBL model and the accompanying instruments (learning modules, instructional syntax, and assessment instruments) were performed through focus group discussions (FGDs) and the Delphi technique. The content validity of the RPjBL model, along with the supporting assessment instruments, was evaluated via Aiken's V analysis. The overall content validity was over 0.87. Reliability for each instrument was measured using Cronbach's alpha; the results indicated very good reliability (all > 0.70). Student assessment data demonstrate that students have a high level of proficiency in laboratory techniques, including the preparation of chemicals and materials (mean = 80.95), chemical handling (mean = 82.86), and performing laboratory procedures (mean = 80.00). Assessment of students' ability to perform the science processes demonstrated exceptionally high proficiency, especially in observing (mean = 88.10) and interpreting data (mean = 90.48). Assessment of students' project performance (using several measures of how well students understood the research process and the quality of their project presentations) had a mean of 75.69. Inferential analysis using Pearson’s correlation indicated a positive, but non-significant, relationship between students’ laboratory and science process skills. Overall, these findings suggest that the RPjBL model has the potential to integrate research-based education and green chemistry into the laboratory experience. Keywords: research-integrated project-based learning, green chemistry, laboratory skills, science process skills.